2020
DOI: 10.20944/preprints202004.0013.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Risk COVID-19: Potential Intervention at Multiple Points in the COVID-19 Disease Process Via Prophylactic Treatment with Azithromycin or Bee Derived Products

Abstract: The pharmacology of azithromycin, and the actions of certain bee products, suggest the possibility of overlap with the pathophysiology of COVID-19 at several points in the disease process. First, intercellular epithelial tight junctions of the respiratory tract serve as a critical barrier to invaders. Pathophysiological factors capable of disrupting this epithelial barrier include viral virulence factors such as those observed for other coronaviruses; virulence factors derived from potentially synergistic path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Activity is based on anaphylactic reaction benefits on metabolism and on organelles, especially those of the respiratory system ( 35 ). Allergens may offer benefits against COVID-19 ( 36 , 37 ); BV can induce elevation of specific IgE and IgG antibodies ( 38 ) and leads to production of IgE antibodies, which can respond to a variety of antigens ( 39 ) ( Table 1 ). Although IgE are responsible for allergic outbursts, they also offer host protective roles over a wide range of allergens ( 39 ).…”
Section: Bee Venom Therapymentioning
confidence: 99%
“…Activity is based on anaphylactic reaction benefits on metabolism and on organelles, especially those of the respiratory system ( 35 ). Allergens may offer benefits against COVID-19 ( 36 , 37 ); BV can induce elevation of specific IgE and IgG antibodies ( 38 ) and leads to production of IgE antibodies, which can respond to a variety of antigens ( 39 ) ( Table 1 ). Although IgE are responsible for allergic outbursts, they also offer host protective roles over a wide range of allergens ( 39 ).…”
Section: Bee Venom Therapymentioning
confidence: 99%
“…As regards the tight junction pathway, we detected 4 genes upregulated and 2 downregulated in DS. Even though the net effect of these deregulations cannot be predicted, interestingly, many viruses, including coronaviruses, disrupt epithelial tight junctions of the respiratory tract that serve as a barrier to invaders (72).…”
Section: Host Proteins Interacting With Viral Proteins Are Enriched Imentioning
confidence: 99%
“…80 The URT is usually the first point of exposure to viral pathogens, hence the modulation of TJ in the mucosal barrier could serve as a potential invasion pathway for pathogens. 81,82 One study observed that the small envelope protein of SARS-CoV binds with the TJ-associated protein PALS1 and delays the formation of the TJ complex, leading to the disruption of lung epithelial morphogenesis. 83 Cytokines such as tumor necrosis factor-α and IFN-γ, which have been associated with TJ disruption, are elevated in SARS-CoV-2 infection.…”
Section: Disruption Of Tight Junction Protein a Potential Mechanismentioning
confidence: 99%
“…Several studies have shown that alterations in transaminase levels in systemic coronaviral infections are transient, and hence may reflect the level of circulating cytokines and the status of immune activation 79 . Considering that histopathological analyses did not identify significant inflammatory damage to the liver, 53,55 it is plausible that liver enzyme alterations in patients infected with SARS‐CoV‐2 are due to bystander hepatitis, which occurs as a secondary response to systemic inflammation by SARS‐CoV‐2.…”
Section: Potential Mechanisms Of Hepatic Abnormalitiesmentioning
confidence: 99%